Chemical characterisation and source apportionment of PM1 during massive loading at an urban location in Indo-Gangetic Plain: impact of local sources and long-range transport. Issue 1 (1st December 2016) - Rajput, Prashant; Mandaria, Anil; Kachawa, Lokesh; Singh, Dharmendra Kumar; Singh, Amit Kumar; Gupta, Tarun
Abstract : This study assesses temporal variability and source contributions of PM1 (particles with aerodynamic diameter ≤ 1.0 µm) samples ( n =51; November 2009–February 2010) from an urban location at Kanpur (26.30°N; 80.13°E; 142 m above mean sea-level) in the Indo-Gangetic Plain (IGP). A study period from November to February is preferred owing to massive loading of particulate matter in entire IGP. PM1 varies from 18 to 348 (Avg±SD: 113±72) µg m −3 in this study. A total of 11 trace metals, five major elements and four water-soluble inorganic species (WSIS) have been measured. Mass fraction of total metals (∑metals=trace+major) centres at 18±14 %, of which nearly 15 % is contributed by major elements. Furthermore, ∑WSIS contributes about 26 % to PM1 mass concentration. Abundance pattern among assessed WSIS in this study follows the order: ≈ > > Cl − . The K-to-PM1 mass fraction (Avg: 2 %) in conjunction with air-mass back trajectories (AMBT) indicates that the prevailing north-westerly winds transport biomass burning derived pollutants from upwind IGP. A recent version of positive matrix factorisation (PMF 5.0) has been utilised to quantify the contribution of fine-mode aerosols from various sources. The contribution from each source is highly variable and shows a strong dependence on AMBT. Events with predominant contribution from biomass burning emission (>70 %) indicate origin of air-masses from source region upwind in IGP. One of the most interesting features of our study relates to the observation that secondary aerosols (contributing as high as ~60 % to PM1 loading) are predominantly derived from stationary combustion sources ( / ratio: 0.30±0.23). Thus, our study highlights a high concentration of PM1 loading and atmospheric fog prevalent during wintertime can have a severe impact on atmospheric chemistry in the air-shed of IGP.